Pentingnya Pengawasan Efektif dalam Mendukung Pengelolaan Keuangan yang Akuntabel pada ISTN Yayasan Perguruan Cikini - Kusumawardhany, Susi; Shanti, Yunita Kurnia; Sudarmadi, Sudarmadi (ASOSIASI IDEBAHASA KEPRI, 2025)
The effective management of financial resources is a fundamental aspect of the success of an organisational unit within a foundation. A unit within a foundation that has effective financial management must be able to demonstrate transparency in its financial operations in order to build trust with the foundation, beneficiaries, and other relevant parties. The presentation of accurate and comprehensive financial reports is an essential component of demonstrating the manner in which the foundation's financial resources are employed. Effective financial management enables management to guarantee that available funds are deployed in accordance with the foundation's mission and objectives. This facilitates the achievement of the desired social impact and ensures the optimal benefit to society. Effective financial management is a key factor in ensuring the financial stability of the unit. By effectively managing cash flow, identifying sustainable sources of income and managing risks in a prudent manner, units can maintain their operational sustainability. Based on the above, we have organised community service at ISTN Perguruan Cikini Foundation, which is a foundation engaged in the field of education. Perguruan Cikini Foundation places a strong emphasis on the accuracy and transparency of its financial reporting, emphasising the importance of effective supervision of financial statements to ensure the foundation's financial accountability..